Penerapan Konvergensi Media Oleh Surat Kabar Harian Singgalang Padang Di Era Digital - Gifa Agathis Redega; Dion Eriend (CV. ITTC INDONESIA, 2025)
The Singgalang newspaper is one of the oldest newspapers in West Sumatra, which faces stiff competition from digital media. Changes in reader behavior and the increasing use of digital technology have influenced the existence of the Singgalang daily newspaper. In this case, the application of media convergence can help the Singgalang daily newspaper increase reader reach and content quality. The Singgalang daily newspaper provides the latest innovation with the emergence of online media. Media convergence theory according to Henry Jenkins, convergence brings together the 3Cs, namely computing (data on computers), communication (communication), and content (content material). The method used in this research is a qualitative descriptive approach. . The techniques used in this research are: interviews, observation and documentation. Analysis activities consist of three activity streams that occur simultaneously, namely data reduction, data presentation and conclusion drawing. Based on data obtained from research results regarding the Implementation of Media Convergence by the Singgalang Daily Newspaper in the Digital Era, the following conclusions can be drawn: In implementing computing, the Singgalang Daily Newspaper uses digital technology to convey information in real-time through various platforms such as websites, Instagram and Facebook, so that readers can access news anytime and anywhere. Communication by using interactive features such as comment, like and share columns, Singgalang Daily can build closer relationships with its audience. The content varies, from viral news to the latest information. The use of various content formats, such as photos, videos and infographics, helps capture the audience's attention and increase their engagement with the news. The supporting factors for Singgalang Daily in implementing media convergence are history and trust as one of the oldest newspapers in West Sumatra. The inhibiting factors for Singgalang Daily are the use of a small server on the website, inadequate human resources and limited budget to support media convergence